2018
DOI: 10.20964/2018.04.01
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acid Extract of Leaves of Juniperus procera on Corrosion Inhibition of Carbon Steel in HCl Solutions

Abstract: The efficiency of the hydrochloric acid leaf extract of Juniperus procera as a corrosion inhibitor against C-steel and its adsorption behavior were investigated in 1.0 M HCl solution using mass loss, potentiodynamic polarization, electrochemical impedance spectroscopy (EIS) techniques. Results revealed that the inhibition efficiency increased with the inhibitor concentration. EIS spectra exhibited one capacitive loop and confirmed the inhibitive capacity. The activation energy (E a ) of the corrosion process c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…So the high corrosion potential values exhibited by the inhibitors proved the inhibitors as good ones. Table 3 and Figures 4(a)-(c) also show a reduction in the corrosion rate and a negligible shift in the corrosion potential (in this case a slight increase) indicating that the inhibitors are mixed type inhibitors [44] [51] [52] [53]. This can also be confirmed from the anodic and cathodic slope values in Table 3.…”
Section: Potentiodynamic Polarization Analysis and Resultsmentioning
confidence: 54%
See 2 more Smart Citations
“…So the high corrosion potential values exhibited by the inhibitors proved the inhibitors as good ones. Table 3 and Figures 4(a)-(c) also show a reduction in the corrosion rate and a negligible shift in the corrosion potential (in this case a slight increase) indicating that the inhibitors are mixed type inhibitors [44] [51] [52] [53]. This can also be confirmed from the anodic and cathodic slope values in Table 3.…”
Section: Potentiodynamic Polarization Analysis and Resultsmentioning
confidence: 54%
“…It also shows that the inhibitors are physically adsorbed on the metal surfaces. The regression values (R 2 ) were very close to unity, an indication revealing the good fitting of the data to the isotherm and the fact that all the adsorbed inhibitor molecules are in contact with the surface layer of the adsorbent (mild steel)[42] [43][44] [56][59]. The slope value for the Langmuir plots is greater than unity, indicating a strong relationship between the species adsorbed.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…Cys. adsorption molecules are found in the MSL interface or solution as a result. Nyquist plots were not close as predicted and revealed a departure from EIS theory. Due to frequency dispersion and the variability of the MSL surface, semicircle mismatch is observed instead of the perfect condition …”
Section: Resultsmentioning
confidence: 99%
“…Also, a concoction prepared from boiled roots and bark is used for cancer treatment by the Kalenjin community in Kenya (Kigen et al, 2017). Studies have also reported that extracts from the plant possess phytochemical compounds like triterpenes, flavonoids, tannins, saponins, and alkaloids (Ali and Suleiman, 2018). Pharmacological studies of extracts have reported the presence of antimalarial, antioxidant, antileishmanial, nematicidal and antibacterial compounds (Mossa et al, 2004;Samoylenko et al, 2008;Alqasoumi and Abdel-Kader, 2012;Samaha et al, 2017).…”
Section: Introductionmentioning
confidence: 99%